Mo2C‐Embedded Carbon Nanofibers as the Interlayer in High‐Performance Lithium‐Sulfur Batteries. Issue 9 (18th February 2022) - Deng, Tongtong; Sun, Wang; Mao, Yuqiong; Huang, Jing; He, Liuliu; Dou, Xinyue; Bai, Yu; Wang, Zhenhua; Sun, Kening
Abstract: Lithium‐sulfur batteries (LSBs) are among the most encouraging competitors for the next‐generation energy storage system, nevertheless, the shuttle effect resulted from the soluble lithium polysulfides (LiPSs) and slow chemical kinetics hinder the pragmatic application of LSBs. To address those issues, herein, a uniform three‐dimensional (3D) structure constructing carbon nanofibers (CNF) with polar Mo2 C nanoparticles (Mo2 C@CNF) was designed and coated onto one side of pristine conventional polypropylene separator (Mo2 C@CNF/PP). The Mo2 C@CNF with high electrical conductivity not only chemically constrained the LiPSs by chemical trapping, but also catalyzed the conversion of LiPSs to Li2 S2 /Li2 S. Cells with Mo2 C@CNF/PP separator presented a high specific capacity of 732.9 mAh g −1 ; 500 mAh g −1 was kept, due to sluggish capacity decay (0.063 % per cycle), after 500 cycles. Judging from the outstanding electrochemical performance of batteries with the Mo2 C@CNF/PP separator, the proposal is an enlightening strategy for the advancement high‐performance LSBs. Abstract : Interlayer : Herein, a uniform three‐dimensional (3D) structure constructing carbon nanofibers (CNF) with polar Mo2 C nanoparticles (Mo2 C@CNF) is designed and coated onto one side of pristine conventional polypropylene separator (Mo2 C@CNF/PP). The proposal is an enlightening strategy for the advancement high‐performance Li−S batteries.